Glocalization trajectories of LGBT identities and politics in China: A review of Queer/Tongzhi China: New Perspectives on Research, Activism, and Media Cultures. Issue 2 (3rd April 2017) - Kama, Amit
ABSTRACT: Queer/Tongzhi China: New Perspectives on Research, Activism, and Media Cultures is a collection of essays that delves into the social, political, and cultural circumstances of contemporary Chinese lesbian, gay, bisexual, and transgender communities and individuals. The collection sheds light on endeavors of a budding and fragile community to pave a path for itself in the face of harsh political and social sanctions.